Cutaneous Squamous Cell Carcinoma, an Immunohistological Analysis - Gull-e-Atif , A H Nagi and Nadeem Afraz , (Journal of Rawalpindi Medical College, 2009)
Background: To detect the presence of keratin in apparently non-keratinizing squamous cell carcinomas by immunoperoxidase staining. This is important because keratinizing tumours are less radiosensitive and non-keratinizing are more radio responsive. Methods: This prospective study was conducted at King Edward Medical College and Post Graduate Medical Institute, Lahore over six months, A total of 45 patients suffering from squamous cell carcinomas of skin were included in the study.Both H and E and immunoperoxidase stainings were performed. Positive and negative controls were set up. The results of both types of staining were compared for each case. Results: Four groups were identified. Nineteen cases showed obvious keratinization on both H and E and immunoperoxidase staining.Eight cases had doubtful keratinization on H and E but showed more obvious keratinization on immunoperoxidase staining. Seven cases were non-keratinizing on H and E staining but revealed keratin on immunoperoxidase analysis.Eleven cases were non-keratinizing on H and E as well as on immunoperoxidase analysis. Conclusion: Immunohistological technique can help us in revising and modifying our H and E impression of a squamous cell carcinoma. It can help us in better diagnosis of squamous cell cancers on basis of keratinization